Effect of particle size of rice flour on physical and sensory properties of Sel-roti - Subba, Dilip (Springer-Verlag, 2011)
Sel-roti is a delicious, deep-fat fried, puffed, ring shaped spongy doughnut like Nepalese indigenous food prepared from the batter of rice flour, ghee and sugar. A study was conducted to determine the effect of particle size of rice flour on bulk density, oil uptake and texture of Sel-roti. Rice was soaked in water and ground with the help of iron mortar and pestle and the flour was analyzed for particle size distribution by using standard sieves and separated into three particle size categories as coarse (> 890 u), medium (120–890 u) and fine (< 120 u). The rice flour of different particle sizes were mixed in different proportions and Sel-roti was prepared from these flours. Bulk density and oil uptake were determined and sensory test was carried out. The results showed significant good positive correlation between mean particle size and bulk density (r = 0.97, p ≤ 0.05) and a good negative correlation between mean particle size and oil-uptake (r = 0.90, p ≤ 0.05). Good positive correlation of mean particle size with texture attributes like hardness (r = 0.99, p ≤ 0.05) and fracturability (r = 0.96, p ≤ 0.05) and good negative correlation with smoothness (r  = -0.97, p ≤ 0.05), cohesiveness (r = -0.92, p ≤ 0.05), stickiness (r = -0.76, p ≤ 0.05) and oily mouth feel (r = -0.85, p ≤ 0.05) and fair positive correlation with chewiness (r = 0.65, p > 0.05) were found.